Oxygen changes crack modes of Ni-based single crystal superalloy - Xueqiao Li (Taylor & Francis Group, 2021)
Oxygen-affected cracking commonly presents on thin Ni-based single crystal superalloy components serving in high temperature and oxidizing environments. This study uses a newly developed in-situ thermal-stress environmental transmission electron microscope to investigate the oxidation and fracture behaviors of Ni-based single crystal superalloy at 650°C under stress. The in-situ oxidation was found to change the tensile fracture mode from the close-packed {111} planes of plastic fracture to $ \{001\} $ planes adjacent to γ/γ′ interfaces of brittle fracture. The microanalysis also revealed that the γ′ cuboids, γ phase, and γ/γ interface exhibit different oxidation behavior, thus underscoring the thickness debit effect.